1989
DOI: 10.1093/nar/17.5.2005
|View full text |Cite
|
Sign up to set email alerts
|

Integration host factor (IHF) stimulates binding of the gpNu1 subunit of λ terminase tocosDNA

Abstract: The lambda terminase enzyme binds to the cohesive end sites (cos) of multimeric replicating lambda DNA and introduces staggered nicks to regenerate the 12 bp single-stranded cohesive ends of the mature phage genome. In vitro this endonucleolytic cleavage requires spermidine, magnesium ions, ATP and a host factor. One of the E. coli proteins which can fulfill this latter requirement is Integration Host Factor (IHF). IHF and the gpNu1 subunit of terminase can bind simultaneously to their own specific binding sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…Insertions between R2 and R1 (7-20 bp) and/or deletion of R1 yield phage phenotypically identical to u cos154 suggesting that IHF obviates the need for the R1 element rather than increasing the affinity of gpNu1 for the site. This is consistent with the observation that IHF does not stimulate gpNu1 binding to the R1 element of u cos154 in vitro [25]. Conversely, while phage with point mutations in the R2 element are similarly IHF dependent for growth, deletion of this element is lethal even in IHF + hosts [96].…”
Section: Review Articlesupporting
confidence: 89%
See 1 more Smart Citation
“…Insertions between R2 and R1 (7-20 bp) and/or deletion of R1 yield phage phenotypically identical to u cos154 suggesting that IHF obviates the need for the R1 element rather than increasing the affinity of gpNu1 for the site. This is consistent with the observation that IHF does not stimulate gpNu1 binding to the R1 element of u cos154 in vitro [25]. Conversely, while phage with point mutations in the R2 element are similarly IHF dependent for growth, deletion of this element is lethal even in IHF + hosts [96].…”
Section: Review Articlesupporting
confidence: 89%
“…Identical footprints are observed in the R3 and R2 region of phage u cos154, but no protection is observed at R1, consistent with the posit that the mutation alters the affinity of gpNu1 for that site [95]. Similar studies have demonstrated that IHF binds strongly to the I1 element in cosB, but only weakly to I2 [26,91,92], and that IHF promotes gpNu1 binding to the R elements [25]. Subsequent studies have demonstrated that point mutations in any of the R elements found within cosB also render the virus IHF dependent for development, with the severity of the mutations following the order R3 \ R2 \ R1 [96].…”
Section: Review Articlesupporting
confidence: 69%
“…A role for IHF in the terminase reaction has been reported previously (43). IHF was reported to bind to several sites in the cos region and imparts a DNA bend of at least 140°c entered at these sites (27).…”
Section: Discussionmentioning
confidence: 62%
“…Replacement of the IHF binding site with intrinsically bent DNA permits efficient X att recombination in the absence of IHF (20). In analogy with IHF stimulation of integrase binding at X att, it has been proposed that IHF induced bending at cos promotes protein-protein contacts between gpNul molecules bound at neighboring sites (27,43 …”
Section: Discussionmentioning
confidence: 99%
“…IHF assists in the utilization of the R sequences by terminase as follows. IHF stimulates ;i assembly in vivo and enhances terminase function in vitro; furthermore many cos mutations render X IHF dependent for plaque formation (Gold and Parris, 1986;Xin and Feiss, 1988;1993;Kosturko etai, 1989;Shinder and Gold, 1989;Mendelson et ai, 1991;Cue and Feiss, 1992a;Xin et ai, 1993). IHF introduces a sharp bend between R3 and R2 (Kosturko etai, 1989), and mutations in 11 abolish IHF stimulation of the X yield (Xin et ai, 1993).…”
Section: Dna-protein Interactions: Interactions Of Gpnui and Ihe Withmentioning
confidence: 99%